The Impact of Artificial Intelligence Adoption on Unethical Recruitment and Selection Practices in the South African Public Sector - Asoba , Samson Nambei; Mefi, Nteboheng Patricia (Journal of Ecohumanism, 2025)
The purpose of this study was to explore the relationship between the level of unethical practices in the recruitment and selection process in the public sector and the level of AI use. To attain this objective hypothesis were developed and analysed. The quantitative approach to research was adopted and the Chi square test of independence was used to test the null hypothesis that: the relationship between the level of unethical practices in the recruitment and selection process in the public sector and the level of AI use is not statistically significant at α=0.05. Seventy-three (73) participants completed a questionnaire to collect data. The analysis that was performed in this study did not find evidence to reject the null hypothesis. Consequently, it was concluded that the adoption of AI does not relate to improved ethical behaviours. The implication of this is that AI also has ethical issues. Essentially, the adoption of AI in the recruitment and selection process may not directly lead to reduction of unethical practices. The study recommends further research to explore how AI can be used or designed to promote ethical recruitment and selection. This recommendation takes note that use of AI remains vital despite any challenges that it may provide.